Karakteristik Sifat Fisika Tanah pada Tegakan Kelapasawit Tanaman Menghasilkan (Studi Kasus di Kebun Rakyat Desa Perlabian Kampung Rakyat Kabupaten Labuhanbatu Selatan) - Anggiat Pangihutan Marbun; Hilwa Walida; Kamsia Dorliana Sitanggang (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2022)
Soil physical properties are the key determinants of the quality of a land and the environment. This study aims to analyze the physical properties of the soil in mature oil palm stands. The method used is a free grid survey method at the semi-detail survey level (observation density of 1 sample per 100 meters). Oil palm soil samples were taken from 6 oil palm sample trees in the people's garden of Perlabian Village, South Labuhanbatu Village, with an area of 1 hectare. The parameters of the physical properties of the soil tested were bulk density, soil porosity, soil color, and soil moisture content. Data analysis was done by descriptive method. The results showed that the physical properties of the soil in the community garden of Perlabian Village, South Labuhanbatu Village, showed good bulk density, clay and firmness, good soil porosity, relatively dark soil color, and high soil moisture content. Therefore, the physical properties of the soil in the people's garden of Perlabian Village, South Labuhanbatu Village are suitable for oil palm growth.. Keywords: Oil Palm, Properties, Physics, Soil